Infrastrukturális beruházások Afrikában – Kína és az új tengeri selyemút - Kis, Katalin (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
Infrastructure deficit is one of the biggest obstacles to economic growth in developing countries. With regard to the built-up infrastructure for transport, telecommunications and energy supply, the African region is poorly performing. In the absence of adequate domestic financing, African countries rely heavily on sources outside the continent. The purpose of the study is to outline possible solutions to the problem of infrastructure deficit in Africa. For this reason, it pays particular attention to the infrastructure development objective of aid and Foreign Direct Investment. Apart from classical donors, the emerging economies, especially China, are already financing Africa’s development. However, China’s perception of Africa is very heterogeneous. In order to ensure more balanced Sino-African relations and the effective functioning of the New Maritime Silk Road, attention should be paid not only to quantitative, but also to qualitative aspects of Chinese developments in the future.